Hey there! The solution to the system is To solve the system, we can multiply the second equation by -1: Then, we add the two equations together, and solve for x: Now, we plug the x value into one of the equations, and solve for y: Now we know that the solution to the system is Hope it helps and have an amazing day! Reply

Answer: (-1/2, 13) Step-by-step explanation: Multiply the 2nd equation by -1, obtaining the following system: 6x + y = 10 -2x – y = -12 —————— Combine like terms, obtaining: 6x + y = 10 -2x – y = -12 —————— 4x = -2 Dividing both sides by 4 yields x = -2/4, or x = -1/2 Substituting -1/2 for x in the second equation yields: 2(-1/2) + y = 12, or -1 + y = 12. Then y = 13, and the solution is (-1/2, 13) Reply

Hey there!The solution to the system isTo solve the system, we can multiply the second equation by -1:Then, we add the two equations together, and solve for x:Now, we plug the x value into one of the equations, and solve for y:Now we know that the solution to the system isHope it helps and have an amazing day!Answer:(-1/2, 13)

Step-by-step explanation:Multiply the 2nd equation by -1, obtaining the following system:

6x + y = 10

-2x – y = -12

——————

Combine like terms, obtaining:

6x + y = 10

-2x – y = -12

——————

4x = -2

Dividing both sides by 4 yields x = -2/4, or x = -1/2

Substituting -1/2 for x in the second equation yields:

2(-1/2) + y = 12, or

-1 + y = 12. Then y = 13, and the solution is

(-1/2, 13)